Figurative Language In Maroon 5 Album Jordi - Selus, Libertus; Ni Made Verayanti Utami; Putu Desi Anggerina Hikmaharyanti (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
This study concerned to know the types of figurative language that found Maroon 5 album Jordi that were released in 2021. There are two problems that formulated by the researcher in this study, they are: (1) what are the types of figurative language that found in song lyrics of maroon 5 album Jordi, (2) what are the meaning of each type of figurative language. There are three theories that used in this study, firstly; the theory that proposed by Knickerbocker and Reninger (1974) in their book entitled Interpreting Literature, secondly; the theory of Leech (1981), in addition used the theory of Halliday and Hasan (1989) to explain the context of situation. In this research the writer found eight types out of ten types of figurative language, they are 2 of simile, 2 of metaphor, 1 of personification, 1 of synecdoche, 1 of metonymy, 1 of hyperbole, 1 of irony.